Editor’s note - Sebolai, Kabelo (Journal for Language Teaching, 2025)
We are very pleased to present our first publication (Vol. 59, no. 1) of the Journal for Language Teaching this year. This publication comes a bit earlier than our first issues in recent years. The reason for this is that although our DHET accreditation requires that we publish at least two issues a year, we have taken a conscious decision to work very hard towards publishing three issues this year. This has been necessitated by our own realization that the journal has grown tremendously in terms of popularity since we moved it to open access in the past three years or so. More and more authors continue to choose the Journal for Language Teaching as the final destination of their scholarly work. Although this is evidence of a boost in the reputation of the journal, it has also resulted in a huge backlog in our review process and consequently, unprecedented and undesired delays in our publications. We acknowledge the inconvenience that this has caused to the authors and apologise for it. We are working very hard to attend to this though. Our decision to get three publications out and to have Vol. 59, no. 1 published so early this year attests to this. We are also in the process of beefing up our editorial team for the purpose of expediting the review process and publications.